Interações corporais que atravessam o tornar-se professor: histórias de vida de três professoras do ensino fundamental - Dal Molin, Ana Paula Barrozo Stefano (2006)
This research intitled historia of life of three teachers of basic education: crossed for corporal interactions: what to know and that to make? is tied to the research line Formation, know ledges and Professional Development, of the Program of Pos-Graduation in Education (PPGE) - Course of Master, of the Center of Education of the Santa Maria Federal University (UFSM). The necessity of control of the man by man unchains the creation of corporal control forms. The development of a greater or minor corporal conscience, on the part of the pupils, this related to the level of corporal conscience of the professor. The school institution has contributed with modelation of these corporeities. Because of this reality, by middle of the work with life histories of three teachers of Santa Maria s region in RS, it reflects about which are the factors that unchained by the school environment, that stands out in the development of the corporal conscience that these teachers present of themselves. Front to this investigation, this research has general objective to investigate which meanings the teachers attribute to the corporal experiences lived in its process of teaching formation. Believing that the experiences lived since of the initial educational period process cross know-to be and know-to make of the professor and understanding that the remembered practical rememorativa makes the interaction between the past and the present possible, I chose the Biographical Method Histories of Life for considering it more appropriate for work with memory. Through the accomplishment of verbal interviews half-structuralized and autobiographic writings guided, the main results were: A) the relationship that the teachers have with the proper corporeities and with of the pupils, the know-making and the aesthetical of the teachers that was more marked its educational process; b) corporal education of the work, still is attributed to the moment of the Physical Education, of playful tricks, games and pedagogical techniques; c) dramatical and musical expression of the subjects in the courses of teaching formation are insufficient for these integrate the daily pertaining to school. The research thematic, the objectives of this, the chosen methodology, the gotten results and the authors who contribute with this work, are presented in this dissertation in five chapters. The first one intitled "corporal Interactions: experiences that stimulate this choice, "enclose the origin of the interest in investigating the thematic of the corporeity and the one brief presentation of this and the questions of research and their objectives - general and specific - of this work. The second chapter, "trecked ways: paths that revisit the corporal marks of the collaborating teachers ", show the chosen methodology, the stages of accomplishment of the work and the scripts of the verbal interview and the autobiographical writing. The third one intitled "corporal Interactions that cross becoming professor: histories of life from three teachers of Basic education", show to the collaborators of the research, the analysis of its moments of corporal education in its process of formation and the influences of these in the constitution of the professional that are being. The fourth chapter "Final Considerations," brings the main "found", the relevance of this thematic to the teaching formation and my learnings in the narrative works and with the thematic of the corporeity; and, finally, the fifth chapter, "bibliographical References", presents the workmanships and authors with their dialogues in this research.